Identificação de papéis ocupacionais e qualidade de vida de pacientes com obesidade - Molinari, Natalia Calil Ambrosio (2017)
Obesity is a common and complex clinical syndrome due to the abnormal or excessive accumulation of body fat in the form of adipose tissue and results in serious health damages, which compromise the performance of the occupational roles and the quality of life of the individuals. Among the techniques for the treatment of obesity is Bariatric Surgery. Objectives: To identify the performance of occupational roles and quality of life of patients with obesity, inserted in the Bariatric Surgery protocol. Method: Cross-sectional and quantitative study, performed at the Bariatric Surgery Outpatient Clinic of a highly complex school hospital. A total of 120 individuals participed, 60 of whom were obese patients who were waiting for the first medical visit in this clinic and 60 individuals of normal weight who were attending patients who were waiting for consultation other medical specialties. For data collection, all participants individually answered the Structured Questionnaire to characterize sociodemographic and clinical data; to the protocol "Role checklist" and the SF-36 Quality of Life Questionnaire. Data collection occurred between the months of September / 2014 to November / 2015. Results: The study group had a mean age of 40.5 ± 10.2, with a predominance of female (80%), morbid (95%), married (53%), active (60%) and hypertension (78%). Regarding the performance pattern of the roles over time, past, present and future, we found a statistically significant difference (p <0.0001) in relation to the present time compared to the other times. Regarding the degree of importance, the most important roles were: worker and family member (97%). And when the quality of life was analyzed, the study group presented all domains impaired in relation to the control group, with statistically significant difference (p <0.0001). Conclusion: Morbid obesity affects the occupational life of these patients, causing significant losses in their roles during the present time. And it impairs the quality of life, especially in the physical realms. Therefore, it is up to the occupational therapist to evaluate and intervene in the promotion and restoration of occupational performance and quality of life.